The psychology of ultra-marathon runners: A systematic review. (July 2018) - Roebuck, Gregory S.; Fitzgerald, Paul B.; Urquhart, Donna M.; Ng, Sin-Ki; Cicuttini, Flavia M.; Fitzgibbon, Bernadette M.
Abstract: Objectives: An 'ultra-marathon' is a footrace over a distance >42.2 km. There is considerable interest in the psychological characteristics of ultra-marathon runners ('ultra-runners') and the psychological effects of running an ultra-marathon. This review aimed to summarise the existing literature concerning the psychology of ultra-runners. Design: A systematic review was performed. Studies were included if they investigated ultra-runners' personality traits, mood, cognitive processes, cognitive function, pain perception, motivations, phenomenology, psychopathology or response to sports psychology interventions. Method: Four databases (PubMed, Scopus, Web of Science and PsycINFO) were searched electronically up until December 2017. Results: Fifty-one studies met the inclusion criteria. A few conclusions regarding the psychology of ultra-runners may be drawn from these studies. First, the acute mood effects of ultra-running appear to include an increase in fatigue and a decrease in vigour and tension. Secondly, the most important factor motivating ultra-runners to engage in their sport appears to be the opportunity to achieve personal goals. Finally, ultra-running seems to be associated with a psychological drive to explore physical and mental limits. Conclusions: Although the existing literature sheds some light on ultra-runners' mood states, motivations and phenomenology, further high-quality studies investigating the psychology of these remarkable athletes are needed. Highlights: The most important factor motivating ultra-runners to engage in their sport is the opportunity to achieve personal goals. Ultra-running is associated with a psychological drive to explore physical and mental limits. Running an ultra-marathon causes an increase in fatigue and a decrease in vigour and tension. These mood changes resolve within one week to one month after the race.